CONSIDERATIONS ON THE PROVISIONS REGARDING FORENSIC EXPERTISE OF THE DRAFT OF CRIMINAL PROCEDURE CODE OF THE RA - Engibaryan, Vahe (State and Law, 2021)
The article is referred to the one of the most important issues of a forensic expertology and criminalistics namely criminal procedural regulation of the institution of forensic examination, comparatively analyzing the provisions of the current Criminal Procedure Code of the RA and the new Criminal Procedure Code of the RA. The article presents new conceptual approaches to the legal status of competent bodies, which are liable to implement judicial examination, their liability as well as the role and basis of the examination conduction. As a result, legal omissions in the existing Criminal Procedure Code of the RA and the Draft of Criminal Procedure Code are revealed. It is noted that the issues identified have both theoretical and practical significance. It is emphasized that within the framework of legal regulation of the draft of the Criminal Procedure Code of the RA examination is presented in a separate chapter as a separate procedural (evidentiary) action in contrast to the current Criminal Procedure Code, in which the appointment and conduct of an examination is regulated as a separate investigative action.